2014
DOI: 10.1371/journal.pone.0109038
|View full text |Cite
|
Sign up to set email alerts
|

Joint Testing of Genotypic and Gene-Environment Interaction Identified Novel Association for BMP4 with Non-Syndromic CL/P in an Asian Population Using Data from an International Cleft Consortium

Abstract: BackgroundNon-syndromic cleft lip with or without cleft palate (NSCL/P) is a common disorder with complex etiology. The Bone Morphogenetic Protein 4 gene (BMP4) has been considered a prime candidate gene with evidence accumulated from animal experimental studies, human linkage studies, as well as candidate gene association studies. The aim of the current study is to test for linkage and association between BMP4 and NSCL/P that could be missed in genome-wide association studies (GWAS) when genotypic (G) main ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
1
12
0
2
Order By: Relevance
“…Liu et al, 2005] and association studies [e.g. Chen et al, 2014]. Furthermore, a gene sequencing study [Suzuki et al, 2009] demonstrated that rare BMP4 coding mutations were enriched in CLP cases at similar frequencies to those shown here.…”
Section: Folate Pathway Variation: Methionine Cycle Genessupporting
confidence: 76%
“…Liu et al, 2005] and association studies [e.g. Chen et al, 2014]. Furthermore, a gene sequencing study [Suzuki et al, 2009] demonstrated that rare BMP4 coding mutations were enriched in CLP cases at similar frequencies to those shown here.…”
Section: Folate Pathway Variation: Methionine Cycle Genessupporting
confidence: 76%
“…Five of our 75 candidate loci with abnormal methylation being BMP4 , ENAH , GALNT2 , and NRP2 and one CpG in a locus without an annotated gene seem to be highly significantly influenced by maternal smoking. Bone morphogenetic protein 4 ( BMP4 ) is of special interest as it is involved in craniofacial development and an important candidate gene for cleft palate defects [ 27 ]. However, BMP4 has not yet been implicated directly in lumbosacral MMC.…”
Section: Discussionmentioning
confidence: 99%
“…RCAS::PI15 upregulated several of these genes that increase the risk of developing human non-syndromic clefts including TP63 (Barbaro et al, 2012;Clements et al, 2010;Kantaputra et al, 2011a), BMP4 (Chen et al, 2014;Kempa et al, 2014;Suzuki et al, 2009;Thomason et al, 2008) and FOXE1 (Ludwig et al, 2014). TBX22 mutations cause cleft palate only in humans (Fu et al, 2015;Kantaputra et al, 2011b;Pauws et al, 2009).…”
Section: Pi15 and The Relationship To Orofacial Cleftingmentioning
confidence: 99%
“…TBX22 mutations cause cleft palate only in humans (Fu et al, 2015;Kantaputra et al, 2011b;Pauws et al, 2009). Most of the mutations in the aforementioned clefting genes are missense mutations with unknown functional consequences (Barbaro et al, 2012;Clements et al, 2010;Kantaputra et al, 2011a;Kantaputra et al, 2011b;Kempa et al, 2014;Suzuki et al, 2009) or polymorphisms associated with clefting (Chen et al, 2014;Ludwig et al, 2014). Thus it is valid to study gain-of-function in the chicken system as a complement to loss of function in the mouse model.…”
Section: Pi15 and The Relationship To Orofacial Cleftingmentioning
confidence: 99%